The conclusion of the deduction of taste in the dialectic of the power of judgment aesthetic in Kant - Manuel Sánchez (Trans/Form/Ação, 2013)
In this paper, it is argued that only in the section on dialectic in the Critique of Judgment does Kant reach a definitive and conclusive version of deduction, after discovering the concept of the supersensible. In the section on the deduction of pure aesthetic judgments, Kant does not satisfactorily explain the critical distinction between the sensible nature of humanity and the supersensible nature of human reason presupposed in the concept of universal communicability. While the concept of the supersensible illustrates this distinction, it is only through this concept that Kant that can justify the specific possibility of claiming subjective validity in taste. The priority of the solution found in the dialectic is illustrated not only by a comparative analysis of the two sections, but also by a historical reconstruction of the process of the formation of the work, which shows that the first formulation of the concept of validity coincides with the use of the concept of the supersensible.